In Vitro Activity of Ceftolozane-Tazobactam and Other Antibiotics against Pseudomonas aeruginosa Infection-Isolates from an Academic Medical Center in Thailand - Woraphot Tantisiriwat; Jirawat Buppanharun; Chatchai Ekpanyaskul; Kwanchai Onruang; Thitiya Yungyuen; Pattarachai Kiratisin; Somchai Santiwatanakul (MDPI AG, 2022)
(1) Background: Resistant Pseudomonas aeruginosa (PA) infections have limited treatment options. Data on the activity of ceftolozane-tazobactam (C-T) against PA in Thailand are limited. Objectives: The objective of this study was to identify the in vitro activity of C-T against general and resistant PA isolates from patients with real clinical infections from the HRH Princess Maha Chakri Sirindhorn Medical Center (MSMC) compared to other antibiotics and to study the resistant molecular patterns of those PA strains which were resistant to C-T. (2) Materials and Methods: This was an in vitro susceptibility study of 100 PA isolates plus an additional seven resistant PA isolates collected from MSMC patients. All PA isolates were tested with susceptibility broth (Sensititre™) and C-T minimal inhibitory concentration (MIC) test strips (Liofilchem, Roseto degli, Abruzzi, Italy). The C-T-resistant PA isolates were analyzed for six β-lactamase genes (blaCTX-M, blaNDM, blaIMP, blaVIM, blaOXA-23 and blaOXA-48) and the mcr-1 gene. (3) Results: A total of 100 PA isolates were collected between January 2020 and January 2021 and between February 2021 and September 2021 for the additional 7 resistant isolates. There were 18 resistant PA isolates (6 MDR, 11 XDR and 1 pan-drug resistant isolate). The overall susceptibility of the initial 100 PA isolates and the 18 resistant PA isolates was 94% and 44.5%, respectively, for C-T. The C-T susceptibility rates for isolates non-susceptible to ceftazidime, piperacillin-tazobactam, carbapenems and antipseudomonal β-lactams were 65.5%, 69.7%, 50% and 44.5%, respectively. Among the 10 isolates which were resistant to C-T, there were only 3 isolates found to have the resistant gene, which included 1 for blaIMP, 1 for blaVIM and 1 for blaNDM. (4) Conclusions: Although C-T was the best susceptibility antibiotic overall for PA isolates and MDR PA isolates at the MSMC, most of the XDR PA isolates and the PDR PA isolate were not susceptible to C-T. The mechanisms for C-T resistance involved multiple factors including the presence of blaIMP, blaVIM and blaNDM.